Substantiation of propitious “Enzybiotic” from two novel bacteriophages isolated from a wastewater treatment plant in Qatar - Ramya Ramadoss (16003318) (2022)
Lysin of bacteriophages isolated from a particular ecosystem could be inducted as a bio-controlling tool against the inhabiting pathogenic bacterial strains. Our study aims at both experimental and computational characterization of the identical lysin gene product inherent in the genomes of two novel Myoviridae bacteriophages, Escherichia Phage C600M2 (GenBank accession number OK040807, Protein ID: UCJ01465) and Escherichia Phage CL1 (GenBank Genome accession number OK040806.1, Protein ID: UCJ01321) isolated from wastewater collected from the main water treatment plant in Qatar. The lysin protein, evinced to be a globular N-acetyl-muramidase with intrinsic “cd00737: endolysin_autolysin” domain, was further expressed and purified to be experimentally validated by turbidimetric assay for its utility as an anti-bacterial agent. Comprehensive computational analysis revealed that the scrutinized lysin protein shared 85–98% sequence identity with 61 bacteriophages, all native to wastewater allied environments. Despite varied Host Recognition Components encoded in their genomes, the similitude of lysins, suggests its apparent significance in host–pathogen interactions endemic to wastewater environment. The present study substantiates the identical lysin from Escherichia Phage C600M2 and Escherichia Phage CL1 as propitious “enzybiotic”, a hybrid term to describe enzymes analogous to anti-biotics to combat antibiotic-resistant bacteria by in silico analysis and subsequent experimental validation. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-022-13171-8